ANALISIS NILAI-NILAI TOLERANSI DALAM KURIKULUM PENDIDIKAN AGAMA - Mujahidil Mustaqim (Jurnal Pendidikan Agama Islam, 2019)
Today's religious tolerance is a very sexy problem with a high sensitivity shock in the midst of a pluralistic society. Religion can be a field of inner conditioning as well as an object of propaganda by certain parties to destroy a civilization. So this article examines what the Islamic Religious Education curriculum looks like in an effort to strengthen religious tolerance. This article was prepared using the library research method. The results showed that the objectives and content of the curriculum in strengthening the attitude of religious tolerance have accommodated the needs and conditions of today's age. The content of the Religious Education curriculum is not dominated by the content of beliefs and worship, but also the content of human relationships such as religious tolerance. Curriculum 2016 Religious Education is considered to have been present to overcome the problem of religious intolerance. So it is not only guarded by citizenship education subjects only. This curriculum analysis is done by examining from two points of view, First, the rationalization of the 2016 curriculum syllabus in religious education. Second, core competencies and material distribution maps are taught as an embodiment of the formation of religious tolerance.